Transient behavior of CHOKe on varying UDP arrival rate - Salleh, Amran (2015)
The Transmission Control Protocol (TCP) is the most widely used in the Internet. It provides an end-to-end reliable transmission of packets and works. However, nowadays many of application used User Datagram Protocol (UDP) as their transport protocols. This is because, UDP more suitable for streaming like video and audio and suited for delay sensitive applications and they are just keeping sending packets the packet even though congestion occur. Presence of UDP in internet, lead to congestion occurs when the aggregated demands for a resource exceeds the available capacity of the resource and create a long delay in data delivery, packet loss and queues overflow. Hence, Active Queue Management (AQM) come into this picture in order to resolve these problems. CHOKe is the best scheme to achieve fair share of bandwidth among flows by penalizing unresponsive flows. Most researchers had done analysis on this scheme under steady state and use constant traffic rate and claim that CHOKe is able to bound both bandwidth share and buffer share of UDP traffic on a link. Therefore, this research going to test CHOKe schemes under transient state by apply UDP traffic rate change over the time. Besides that, a modified CHOKe was developed to enhance a shortcoming of existing CHOKe. A modified CHOKe has shown a 95% confidence interval (CI) under transient state found the results of modified CHOKe are able to reduce 5.16% of capacity link bandwidth utilization compared to original CHOKe.